2019
DOI: 10.1111/ffe.12982
|View full text |Cite
|
Sign up to set email alerts
|

High cycle fatigue life estimation of materials processed by laser powder bed fusion

Abstract: The fatigue life of metal components is known to depend on the surface topography. For components made by laser powder bed fusion, the roughness of the as‐built surfaces depends on the orientation of the component surface with respect to the build plate. Surface topographies of AlSi10Mg and Inconel 718 specimens built at 0° to 90° inclination, with 15° increments, were characterised by white light interferometry. Two methods for calculating the stress concentration factor using the surface roughness data are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In addition to AM process parameters, design parameters—such as build orientation and scanning pattern—can also affect the thermal history . Consequently, AM parts can have more anisotropic behaviour than their wrought counterparts since the final mechanical performance of fabricated parts is directly related to the thermal history‐dependent microstructure …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to AM process parameters, design parameters—such as build orientation and scanning pattern—can also affect the thermal history . Consequently, AM parts can have more anisotropic behaviour than their wrought counterparts since the final mechanical performance of fabricated parts is directly related to the thermal history‐dependent microstructure …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Consequently, AM parts can have more anisotropic behaviour than their wrought counterparts since the final mechanical performance of fabricated parts is directly related to the thermal history-dependent microstructure. 2,[16][17][18] Historically, requirements of the parts' durability under cyclic loading (ie, fatigue) proved to be one of the most challenging ones to meet, particularly for new materials and manufacturing technologies such as AM. 5 The amount and distribution of anomalies and residual stresses as well as other microstructural features (eg, grain size and crystallographic texture)-as a consequence of non-uniform thermal history of each point during AM process-play a crucial role in fatigue behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A certain amount of small defects ( Figure 6B) are hardly detected by micro-CT. Some studies have been conducted about the impact of defects on the fatigue behaviors of metal additive manufacturing parts [16][17][18]. It can be concluded that the detectability of small defects in SLM parts is more critical and demands a high resolution CT scan (highly recommend voxel size < 7 µm) or other auxiliary porosity identification methodologies.…”
Section: Characteristics Of Ebm Specimensmentioning
confidence: 99%
“…They significantly influence the static and dynamic mechanical properties of a material including fatigue strength. Several studies have been carried out recently to assess the fatigue behavior of different AM materials, that is, AlSi10Mg [9][10][11][12], Ti6Al4V [13][14][15][16][17][18], Ni-based alloy [19], 15-5 PH stainless steel [20], steel [21], stainless steel [22]. Nasab et al [23] studied the effect of surface and subsurface defects on the fatigue behavior of AlSi10Mg.…”
Section: Introductionmentioning
confidence: 99%